Effect of Price Promotion and Quality Service On Loyalty Customers At PT. Media Antar Nusa (Nusanet) Medan - Matthew Yesaya Simanjuntak; Indah Puspitasari Simanungkalit; Annisa Fimadita; Bilbao Carlos Napitupulu; Nurmaidah Ginting (CERED Indonesia Institute, 2022)
Study this that is descriptive quantitative. Using the Research model Quantitative approach study this. The population in the study is as many as 600 customers, which includes whole consumers at PT. Media Antar Nusa (Nusanet) Medan. The researcher also use 30 customers moment To do testing validity and reliability and 86 customers for the testing sample. Test the hypothesis can be using models regression multiple. However before analysis linear regression is obtained, moreover first the model tested assumption classic of them covers testing normality, multicollinearity, and heteroscedasticity. Research conclusion this is at a time Becomes results where is the price worth 2,670 with score significant 0.009 shows that by Partial affected significant to Loyalty Customers at PT. Media Antar Nusa (Nusanet) Medan. Promotion worth 2,172 with a score significant of 0.033 shows that Partial affected significantly to Llty Customers at PT. Media Antar Nusa (Nusanet) Medan. Quality Service worth 1.391 with a score significant of 0.168 shows that by Partial no affected to Loyalty Customers at PT. Media Antar Nusa (Nusanet) Medan. Price, Promotion, and Quality Service worth 5,548 with a level significant of 0.002 in simultaneous existence influence significant to Loyalty Customers at PT. Media Antar Nusa (Nusanet) Medan